Formulation of a novel anti-human oral squamous cell carcinoma supplement by gold nanoparticles-Kaolin nanocomposite. Issue 1 (31st December 2022) - Dong, Weijie; Zhang, Juan; Zhuang, Ziyun; Zhong, Jiayong; Zhang, Jianming
Abstract: In this work, we have described the biogenic synthesized gold nanoparticles being supported over Kaolin mediated by Pomegranate peel extract as natural reducing and stabilizing agent under mild conditions without any toxic reagents. Pomegranate peel extract was used as a green reducing agent and an excellent stabilizer of the synthesized Au NPs. Physicochemical characterization of the as-synthesized Kaolin@extract/Au NPs nanocomposite was carried out through electron microscopy (SEM and TEM), energy dispersive X-ray spectroscopy (EDX), elemental mapping, X-ray diffraction (XRD) and inductively coupled plasma-optical emission spectroscopy (ICP-OES). In the cellular and molecular part of the recent study, the treated cells with Au NPs-Kaolin nanocomposite were assessed by MTT assay for 48 h about the cytotoxicity and anti-human oral squamous cell carcinoma properties on normal (HUVEC) and oral squamous cell carcinoma cell lines i.e. HSC-2, HSC-3, HSC-4 and Ca9-22. It has been observed that the Au NPs with spherical shape and size were dispersed homogeneously on the modified-Kaolin surface. The significance of this study is the novel initiative to combine the gold nanoparticle with inexpensive Kaolin clay and utilization of them as anticancer agent. The IC50 of Kaolin@extract/Au nanocomposite were 277, 367, 250 and 545 µg/mL against HSC-2, HSC-3, HSC-4 and Ca9–22 cell lines, respectively. The viability of malignant human oral cell lines reduced dose-dependently in the presence of Kaolin@extract/Au NPs nanocomposite.